Layered P2-Na2/3[Ni1/3Mn2/3]O2 as high-voltage cathode for sodium-ion batteries: The capacity decay mechanism and Al2O3 surface modification. (September 2016) - Liu, Yihang; Fang, Xin; Zhang, Anyi; Shen, Chenfei; Liu, Qingzhou; Enaya, Hani A.; Zhou, Chongwu
Abstract: The P2 type Na2/3 [Ni1/3 Mn2/3 ]O2 is a high-voltage cathode material for Na-ion batteries with a theoretical capacity of 173 mA h/g and a long operation voltage plateau of 4.2 V. However, the material has exhibited unstable cycling performance within the high-voltage window, which severely limits its application. Moreover, its capacity decay mechanism is still unclear. In this study, we first investigate the difference between as-prepared and after-cycling Na2/3 [Ni1/3 Mn2/3 ]O2 samples, and then confirmed that the transition metal oxide layer exfoliation associated with the crystal phase transition during Na ion extraction and insertion is the main cause of capacity fading. The Al2 O3 coated Na2/3 [Ni1/3 Mn2/3 ]O2 with enhanced cycling performance was prepared by taking the benefit of Al2 O3 coating. The Na2/3 [Ni1/3 Mn2/3 ]O2 sample without any surface modification presented a 164 mA h/g initial specific discharge capacity within the voltage window from 2.5 V to 4.3 V, and the capacity decayed to 44 mA h/g at the 300th cycle, resulting in only a 26.8% retention. In contrast, the Al2 O3 -coated Na2/3 [Ni1/3 Mn2/3 ]O2 presented a similar initial capacity, but with an enhanced 73.2% retention after 300 cycles. The enhanced cycling stability observed in after-cycling characterization and analysis confirms that the Al2 O3 surface coating can effectively suppress the unfavorable side reaction at high voltage and the exfoliation of the metal oxide layers. Graphical abstract: Highlights: Al2 O3 coated P2 type Na2/3 [Ni1/3 Mn2/3 ]O2 is demonstrated to be a stable and high energy density cathode for sodium-ion batteries. Transition metal oxide layer exfoliation associated with crystal phase transition was confirmed to be the main reason of the capacity fading. The surface modification cannot only reduce the side reaction at high voltage, but also can give mechanical support to help the bulk material to maintain the layered structure.